Development of a low cost photovoltaic/thermal solar concentrator for building integration (BIPVTC) - Kunnemeyer, R; Duke, M; Anderson, TN; Carson, JK (Australian Solar Energy Society Ltd, 2011)
The idea of concentrating solar energy to increase the output of photovoltaic and solar thermal collectors is an area that has received significant attention. However, the use of solar concentrators that form part of a building’s fabric is an area that has received little attention to date. In this study, the design of a novel building integrated photovoltaic/thermal solar concentrator (BIPVTC) is discussed. The design is theoretically analysed and the model validated with experimental data. The results show that BIPVTC offers improved electrical yields from both concentrating radiation onto the photovoltaic cells and also by actively cooling them. Also, it was shown that the BIPVT could be made of a durable (long life) stainless steel, rather than the more reflective aluminium, while still offering a noticeable increase in annual output.
Keywords: Building integrated; Concentrator; Photovoltaic/thermal